2020
DOI: 10.38150/sajeb.10(5).p301-312
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of vitamin E on aluminium chloride-induced liver and kidney damage in rats

Abstract: Aluminium is present in many manufactured foods and medicines and is also used in water purification. It is known that aluminium causes oxidative stress. Therefore, the present study was undertaken to determine the effectiveness of vitamin E (VE) in modulating the toxicity of aluminium chloride (AlCl3) on biochemical parameters, antioxidant enzymes and lipid peroxidation in serum and different organs (liver and kidney) of male Wistar rats. 24 rats (150-180g) were divided into four groups of six animals each : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…This reduction in catalase activity indicates an increase vulnerability or susceptibility of these flies to oxidative stress and damage (Fridovich and Freeman, 1986). In this study, a significant increase in catalase activity was observed in flies co-treated with Vitamin E and AlCl3when compared with those treated with AlCl3 only thus further justifying the free radical scavenging properties and antioxidant potential of Vitamin E. Similar findings on the ability of Vitamin E to improve CAT and SOD activities following AlCl3 has been previously reported in rats by Lablack et al (2020).…”
Section: Discussionsupporting
confidence: 90%
“…This reduction in catalase activity indicates an increase vulnerability or susceptibility of these flies to oxidative stress and damage (Fridovich and Freeman, 1986). In this study, a significant increase in catalase activity was observed in flies co-treated with Vitamin E and AlCl3when compared with those treated with AlCl3 only thus further justifying the free radical scavenging properties and antioxidant potential of Vitamin E. Similar findings on the ability of Vitamin E to improve CAT and SOD activities following AlCl3 has been previously reported in rats by Lablack et al (2020).…”
Section: Discussionsupporting
confidence: 90%